Recurrent statin-induced rhabdomyolysis: Commonly overlooked drug (Indian Journal of Case Reports, 2024)
Statin-induced muscle pain and myopathy are common. However, statin-induced rhabdomyolysis causing severe nephropathy is somehow uncommon. Here, we present the case of a 68-year-old patient on statin therapy after percutaneous coronary intervention. We want to highlight the fact that physicians should differentiate muscle pain without biochemical derangement and with severe rhabdomyolysis leading to acute kidney injury and hyperkalemia. Patients should be made aware of this commonly overlooked drug causing severe complications.